2015
DOI: 10.1111/sms.12478
|View full text |Cite
|
Sign up to set email alerts
|

Alpine Skiing With total knee ArthroPlasty (ASWAP): metabolism, inflammation, and skeletal muscle fiber characteristics

Abstract: We investigated the effect of alpine skiing for 12 weeks on skeletal muscle characteristics and biomarkers of glucose homeostasis and cardiovascular risk factors. Twenty-three patients with a total knee arthroplasty (TKA) were studied 2.9 ± 0.9 years (mean ± SD) after the operation. Fourteen patients participated in the intervention group (IG) and nine in the control group (CG). Blood samples and muscle biopsies were obtained before (PRE) and 7.3 ± 0.8 days after (POST) the intervention, and blood samples agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
3
5
1
1
Order By: Relevance
“…Furthermore, as eccentric tensile load seems particularly effective to increase Lf (Reeves et al., ), such an increase was expected with downhill skiing training. The explanation for this discrepancy is unclear, but our ultrasound measurements are consistent with the lack of evidence of VL muscle hypertrophy in biopsy samples collected in the same patients (Kristensen et al., ). A possible explanation may be related to regional differences in muscle hypertrophy (Wells et al., ) and the different muscle areas that were scanned by Narici et al.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, as eccentric tensile load seems particularly effective to increase Lf (Reeves et al., ), such an increase was expected with downhill skiing training. The explanation for this discrepancy is unclear, but our ultrasound measurements are consistent with the lack of evidence of VL muscle hypertrophy in biopsy samples collected in the same patients (Kristensen et al., ). A possible explanation may be related to regional differences in muscle hypertrophy (Wells et al., ) and the different muscle areas that were scanned by Narici et al.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, muscle contraction forces in alpine skiing seem adequate and effective to increase leg muscle strength in the weaker OP leg. The strength improvements in the present study seem to be mainly based on hypertrophy of the rectus femoris as shown by Rieder et al () while no change could be observed in the vastus lateralis (Kristensen et al., ; Rieder et al., ).…”
Section: Discussionsupporting
confidence: 65%
“…Activation of the inflammatory pathway can indeed lead to a reduction in protein synthesis through inhibition of the AKT‐mTOR‐p70s6K pathway but also stimulate protein breakdown through the NF‐κΒ‐mediated release of inflammatory cytokines leading to activation of the MURF1 and MAFbx (Kumar et al., ). Although systemic inflammation in these patients was found to be within the normal range (see Kristensen et al., ) both before and after training, the possibility of raised local muscle inflammation cannot be excluded. In fact it has been reported that aging is associated with muscle inflammation susceptibility (Merritt et al., ) and we recently hypothesized that local inflammation is more important than the systemic one for the inflamm‐aging effects to occur (Salvioli et al., ).…”
Section: Discussionmentioning
confidence: 77%